2019
DOI: 10.1063/1.5054649
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing terahertz generation from a two-color plasma using optical parametric amplifier waste light

Abstract: We show experimentally that the terahertz (THz) emission of a plasma, generated in air by a two-color laser pulse (containing a near IR frequency and its second harmonic), can be enhanced by the addition of an 800-nm pulse. We observed enhancements of the THz electric field by a factor of up to 30. This provides a widely accessible means for researchers using optical parametric amplifiers (OPA) to increase their THz yields by simply adding the residual pump beam of the OPA to the plasma generating beam. We inv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The use of first and second harmonics in two-color lasers leads to more intense THz waves. In confirmation of these results, Sorenson et al [24] showed experimentally that the electric field of THz emission and the radiated power enhanced in interaction of two-color femtosecond laser pulses with plasma. The utilization of laser pulse second harmonic in a two-color scheme leads to more intense THz radiation.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The use of first and second harmonics in two-color lasers leads to more intense THz waves. In confirmation of these results, Sorenson et al [24] showed experimentally that the electric field of THz emission and the radiated power enhanced in interaction of two-color femtosecond laser pulses with plasma. The utilization of laser pulse second harmonic in a two-color scheme leads to more intense THz radiation.…”
Section: Resultsmentioning
confidence: 77%
“…In this section, the generation of THz waves resulting from the interaction of two-color femtosecond laser pulses in magnetized and collisional plasma in a relativistic regime is investigated. In order to demonstrate the theoretical predictions, the following THz generation in magnetized and collisional plasma was considered using the following parameters listed in [23] and [24]: laser spot size r L = 50 μm and laser pulse duration τ L = 100 fs. In the interaction of two-color laser pulses with plasma, the first and second harmonics of the laser beam copropagate into the plasma media simultaneously leading to acceleration of plasma electrons by the laser fields.…”
Section: Resultsmentioning
confidence: 99%
“…The above model may seem complicated to use: iterations in the expressions ( 6), (11) and ( 13) look unwieldy. However, in many cases these expressions can be simplified.…”
Section: Numerical Calculations and Discussionmentioning
confidence: 99%
“…Within this range, several different subranges can be distinguished, each of which is relevant for different applied areas; as a rule, such ultrashort pulses are in demand for ultra-precise measurements and spectroscopy [6,7], control of various quantum or chemical processes [8,9], biomedical imaging [10], while the possibility of frequency tuning further expands the range of applicability of such sources. This can be done using the frequency tuning of the ionizing pulse components in optical parametric generators [11][12][13]. Recently, the possibility of using multi-color (three or more) pulses instead of traditional two-color ionizing pulses has been increasingly investigated [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…With this perception, the operator can undoubtedly make extremely accurate and efficient judgments, and better control the waveform simulation of dual-color laser field imaging. Based on this characteristic, it is assumed that augmented reality technology can be applied to the waveform simulation of dual-color laser field imaging, which can significantly improve the application and operating efficiency of the laser waveform simulation control process [20]. First of all, the use of augmented reality technology can achieve two transformations, making the operation process more intuitive and concise.…”
Section: Application Based On Augmented Reality Technologymentioning
confidence: 99%